Association of dietary phytochemical index with metabolically unhealthy overweight/obesity phenotype among Iranian women: A cross-sectional study - Pourreza, Sanaz; Mirzababaei, Atieh; Naeini, Fatemeh; Naghshi, Sina; Mirzaei, Khadijeh (Frontiers in Nutrition, 2022)
Background: Phytochemicals have been recently studied as adjuvants for the treatment of obesity. No study has investigated the association of phytochemical-rich foods with metabolically unhealthy overweight/obesity phenotype (MUOW/O). This study aimed to determine the association of dietary phytochemical index (DPI) with MUOW/O based on Karelis criteria among Iranian female adults. Methods: In this cross-sectional study, a total of 228 overweight and obese women aged 18-48 years old were included. Anthropometric measurements were evaluated for all participants. A validated 147-item food frequency questionnaire (FFQ) was used for dietary assessment. DPI was calculated as (dietary energy derived from phytochemical-rich foods (kcal)/total daily energy intake (kcal)) × 100. Participants' body composition and biochemical parameters of Karelis criteria (triglyceride [TG], high-density lipoprotein cholesterol [HDL-C], low-density lipoprotein cholesterol [LDL-C], insulin, and high-sensitivity C-reactive protein [hs-CRP]) were determined. Results: The mean age of the study participants was 36.69±9.20, and the mean DPI score was 26.23±9.48 among participants with MUOW/O phenotype. After controlling for potential confounders, women in the highest tertile of DPI had lower odds for MUOW/O phenotype (odds ratio [OR]:0.23, 95% confidence interval [CI]: 0.07-0.68, P=0.008) compared to the lowest tertile. Among the components of Karelis criteria, homeostatic model assessment for insulin resistance (HOMA-IR) was significantly associated with MUOW/O phenotype in the fully adjusted model (OR:0.29, 95% CI:0.10-0.79, P=0.01). Conclusions: We found a significant association between DPI and MUOW/O phenotype in Iranian women. Prospective studies are needed to confirm these findings.